STUDI PERBANDINGAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL NHT DAN MODEL MIND MAPPING - Esa Norita; Eddy Purnomo; Yon Rizal (FKIP Unila, 2013)
The aimed of this research was to know how effective cooperative learning models type Number Head Together and Mind Mapping in subject of IPS Terpadu. NHT in experiment class and Mind Mapping in controll class.Methods used in this research was comparative research with experiment approach. The population was all students class VIII in Junior High School 18 Bandar Lampung as many as 399 students with total sample is 74 students, taken by cluster random sampling techniques. The techniques to collected data used observation, documentation, inquiry, and test. Hypotesists used Anava and T-test Two Sample Independen. Based on result analyses showed that (1) there was any different average result of study for students who learn with cooperative learning NHT and Mind Mapping. (2) there was any different average result of study for students who have positive attitude with cooperative learning NHT was higher than Mind Mapping. (3) there was any different average result of study for students who have negative attitude with cooperative learning NHT was higher than Mind Mapping. (4) there was not any interaction between cooperative learning models and student’s attitude on subject learning.Kata Kunci: NHT, MM, sikap, hasil belajar.